Quality in the analysis of health situation: a non-achieved goal - Narciso Águila Rodríguez; Eneida Bravo Polanco (Medisur)
Analyzing the health situation is a core research in the Primary Health level, since it studies health and its determinants aimed at determining the appropriate ways for problem solving inn the same scenario where they arise and develop. There are, however, difficulties in in its implementation , which are based both on false conceptions about its usefulness and ignorance about the correct way to do it. The objective of this work is to reflect about the difficulties that still persist in their realization.